Restorative Juvenile Justice: Level of Implementation and Level of Awareness among Residents in Tangub City - Anas, Joel L.; Pallega, Rowell B.; Bandigan, Elaine Y. (Future Science / FSH-PH Publications, 2022)
This study aimed to determine the level of implementation and awareness of the juvenile restorative justice program in Tangub City during calendar year 2018-2019. This study made use of non-experimental quantitative research design utilizing descriptive, frequency count, percentage and mean. On the level of implementation of the program, the community respondents exhibited low level of response while the Philippine National Police and the CSWD exhibited a high level of responses. On the level of awareness, the respondents also exhibited a high level of response. It is recommended that the implementers may include or emphasize the community's active participation in juvenile restorative programs. This will encourage them to get involved and recognize the importance of their engagement, maybe resulting in fewer minor-related offenses. The implementers may look into the process on the way the programs are implemented. This will encourage them to examine probable flaws in the execution of the juvenile restorative justice program in order to make adjustments to the overall process of implementation, which could lead to the program's overall success. The implementers may consider looking into the victim's need for reformation and rehabilitation, as well as their family's general engagement. This is critical to ensure that the victims and their families believe the government is on their side, because if the implementers neglect this, retaliation may ensue. Further studies are warranted.